PHYTOCHEMICAL SCREENING AND HISTOLOGY APPEARANCE OF ACUTE ORAL TOXICITY STUDY ON ETHANOL EXTRACT OF PSIDIUM GUAJAVA LINN. FRUIT IN MICE - Atik, Nur; Muda, Iskandar; Rahmadi, Andri Reza; Achadiyani, Achadiyani; Djunaedi, Diah Dhianawaty (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objectives of the research are to investigate the phytochemical screening, histology appearance, and safety of acute oral toxicity study on the extract of the fruit of Psidium guajava Linn. in mice. Methods: Mice that were administered by oral feeding with different and controlled dose were divided into three groups, with dose limits of both 2000 and 5000 mg/kg b.w. We analyzed the P. guajava Linn. extract with specific methods before treating the subject. The methods were followed with acute oral toxicity study of Up-and-Down Procedure Organization for Economic and Development 425. The mice were then observed for signs and symptoms of toxicity. In addition, toxicity in the liver and kidney was analyzed through histology observation. Results: Phytochemical screening revealed the presence of flavonoids, quinone, triterpenoid/steroid, tannins and saponins, and the absence of alkaloids. We found that the treatment with 2000 and 5000 mg/kg b.w. of the extract did not show any differences in body weight changes, number of hepatocyte in liver, and podocyte in kidney compared with control (*p>0.05). Moreover, we noticed all mice lived and were healthy during observation. Conclusion: Our finding indicates that the extract of the fruit of P. guajava Linn. is safe and it was not toxic to the liver and kidney.